Towards a new paradigm for rural extensionists’ in-service training - Landini, Fernando Pablo (2017)
Changes in the conceptions of extension and rural innovation, as well as the persistence of diffusionist extension approaches, require rethinking training strategies for rural extensionists. Drawing upon conceptual insights pertaining to the theory of action, the social learning theory, and the communities of practice framework, in this paper, current training and educational strategies for extensionists will be critically reflected upon, lessons learnt will be extracted, and proposals will be generated. Amongst them, the need for expanding and reframing what we understand ‘training extensionists’ to be, overcoming the traditional transfer-of-knowledge approach, focusing on the reflection on practice process, supporting the horizontal exchange of knowledge and experiences, and facilitating the development of extensionist communities of practice, are highlighted. Finally, it is argued that there is a need for advancing the conceptual discussion, systematizing innovative training practices, and researching trainings for extensionists and their impact.